The Stuff of nightmares - Blackman, Malorie; local; Corgi Books (London : Corgi Books, 2008)
Kyle has always been afraid of things, especially dying. But when he gets on the train that is taking him and his class on a school trip, he has no idea how close to Death he is going to come. Death enters the train and Kyle moves with him, past his friends, who are frozen in time, in life-or-death situations. Kyle finds that he can pick up on their deepest, darkest fears - real things that have happened to them, or may happen in the future, and sometimes their surreal nightmares too.
Keywords: Nightmares -- Fiction; Suspence fiction